New Insights Into the Effects of Individual Chinese Herbal Medicines on Chronic Kidney Disease - Shao, Minghai; Ye, Chaoyang; Bayliss, George; Zhuang, Shougang (Frontiers in Pharmacology, 2021)
The clinical and experimental study into the effects of Chinese herbal medicines on chronic kidney disease has evolved over the past 40 years with new insight into their mechanism and evidence of their clinical effects. Among the many traditional Chinese herbs examined in chronic renal disease, five were found to have evidence of sufficient clinical efficacy, high frequency of use, and well-studied mechanism. They are: Abelmoschus manihot and Huangkui capsule， Salvia miltiorrhiza and its components (tanshinone II A, salvianolic acid A and B); Rhizoma coptidis and its monomer berberine; Tripterygium wilfordii and its components (triptolide, tripterygium glycosides); Kudzu root Pueraria and its monomer Puerarin. These Chinese herbal medications have pharmaceutical effects against fibrosis, inflammation and oxidative stress while also promote renal repair and regeneration. This article reviews their clinical efficacy, anti-fibrotic effects in animal models, and molecular mechanism of action.